2014
DOI: 10.3109/01612840.2014.930216
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Housing and Housing Support for People with Psychiatric Disabilities

Abstract: The aim of this study was to investigate the degree of satisfaction with housing and housing support for people with psychiatric disabilities in Sweden. A total of 370 residents, in supported housing and in ordinary housing with housing support, completed a new questionnaire and reported a high degree of overall satisfaction, but many of them wanted to move somewhere else. Differences were found between the two different types of housing concerning satisfaction with housing support, social life and available c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 18 publications
12
31
0
Order By: Relevance
“…On the other hand, loneliness was among the worst. This latter finding concurs with previous studies in which social isolation and loneliness have been found to be common problems among people with psychiatric disabilities . The two findings from this study pinpoint a dilemma.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the other hand, loneliness was among the worst. This latter finding concurs with previous studies in which social isolation and loneliness have been found to be common problems among people with psychiatric disabilities . The two findings from this study pinpoint a dilemma.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, further research is needed in order to explore more nuances. Yet, the free format of the questions provided the respondents with the opportunity to freely express themselves, which revealed aspects and nuances that were not shown in the SHPD survey . The findings in ordinary housing about feeling safe and secure at home, but insecure in the neighbourhood, constitute a nuanced distinction from the residents’ satisfaction with security and privacy shown in the SHPD survey .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As in previous studies,6–10 participants said that they felt safer knowing they could ask staff for help in challenging situations and they considered their life as easier. At the same time, they were worried about being different from ordinary people, as also appeared in the study of Bengtsson-Tops et al9 So, is life safer and easier in supported houses because residents do not have to deal with certain difficult situations or is it because they get help finding their own strategies of coping with challenging situations?…”
Section: Discussionsupporting
confidence: 57%